Development and commercialization of reduced lignin alfalfa. (April 2019) - Barros, Jaime; Temple, Stephen; Dixon, Richard A
Abstract : Reducing lignin content in forage legumes can improve digestibility and, correspondingly, animal performance, and alfalfa ( Medicago sativa ) is the first genetically engineered crop commercialized for improved forage digestibility. Lignin reduction was achieved by downregulating the gene encoding caffeoyl-CoA 3- O -methyltransferase (CCoAOMT), and development of the commercial product, branded as HarvXtra, required the coordination of two research institutions and two companies, and more than 15 years of research and field trials. Lignin modification has positive impacts on forage management. Future developments will likely stack lignin modification with additional forage quality traits.